Successful Third Hematopoietic Stem Cell Transplantation for Blast Crisis of Chronic Myeloid Leukemia After Two Times of Graft Failure - Keigo Sano; Aki Fujii; Ryosuke Fujiwara; Mariko Fujita; Shuji Minamoto; Keiko Yamazaki; Hideo Yagi; Kazuo Tsubaki; Hitoshi Hanamoto (Internal Medicine, 2017)
Background: Chronic Myeloid Leukemia (CML) is largely treated with BCR-ABL protein targeted drugs called tyrosine kinase inhibitors (TKIs) , imatinib, which have led to dramatical improvement in 2001. Nilotinib and dasatinib were approved as the second new TK inhibitor in 2010, and Radotinib in 2012. However, the only curative treatment for CML is a bone marrow transplant or an allogeneic stem cell transplant. Case: A 42-year-old man was diagnosed CML in June 2011. He had achieved complete cytogenetic response in 5 months later by nilotinib treatment. It did not lead to major molecular response in the 18th month, and blastic phase of acute promyelocytic leukemia (M3) occurred in the 19th months. Leukemia cells had both promyelocytic leukemia gene/retinoic acid receptor alpha (PML/RARα) and BCR/ABL translocations. A retinoic acid was administered for M3. The dasatinib was administered for the blast crisis, and remission was obtained. Transplantation: Hematopoietic stem cell transplantation (HSCT) from umbilical cord blood was performed at remission, but it was rejected twice. The third HSCT was succeeded from a sister who had hyperthyroidism. Conclusion: After 2 times of graft failures, HSCT was succeeded. Long plan of treatment is necessary for middle aged CML patients.